Pengetahuan dan Kepatuhan Minum Obat Antidiabetik pada Pasien Diabetes Melitus Tipe II - Endah Purwanti; Mimin Mintarsih; Bekti Sukoco (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the relationship between patient knowledge about diabetes mellitus and adherence to taking antidiabetic medication. The method used in this research is quantitative non-experimental with a cross-sectional approach. The results showed that most respondents had a low knowledge of 77.1% and a high compliance rate of 47.9%. Based on the Spearman Rank correlation test, the correlation coefficient value was 0.354*. In conclusion, there is a significant relationship between the level of knowledge of diabetes mellitus and adherence to taking antidiabetic medication. Keywords: Diabetes Mellitus; Medication Compliance, Knowledge